Essays on the Economics of Suspense, Surprise, Superstars, and Soda - Kaplan, Scott M. (online, 2021)
Economists have always been interested in understanding and estimating demand for different goods. Demand is affected by a number of factors, but one that is very important is information. In this work, I estimate the impacts of both instrumental and non-instrumental information on demand for important and commonly consumed products. Instrumental information is information received by an agent that leads to a contingent action. For instance, receiving information about the negative health effects of consuming sugar sweetened-beverages may affect an agent's decision about how many sugar-sweetened beverages they consume. On the other hand, non-instrumental information is information consumed for the sake of entertainment and attention-capture. For example, information disseminated through the news or a novel may not lead to any direct actions, but is enjoyable and welfare improving nonetheless. My dissertation aims to explore the economic implications of demand in response to information.Chapter one, titled Entertainment Utility from Skill and Thrill, uses revealed preference methods to estimate demand for non-instrumental information in entertainment. I do this by examining the
Keywords: Graue Literatur; Hochschulschrift; Aufsatzsammlung; Research; Decision making; Tournaments & championships; Election results; Probability; Prices; Literature reviews; Ratings & rankings; Professional basketball; Seminars; Political advertising; Applied microeconomics; Consumer attention; Entertainment; Information; Sugar-sweetened beverages; Willingness to pay